2022
DOI: 10.1038/s41467-022-28926-0
|View full text |Cite|
|
Sign up to set email alerts
|

Atomistic insights into highly active reconstructed edges of monolayer 2H-WSe2 photocatalyst

Abstract: Ascertaining the function of in-plane intrinsic defects and edge atoms is necessary for developing efficient low-dimensional photocatalysts. We report the wireless photocatalytic CO2 reduction to CH4 over reconstructed edge atoms of monolayer 2H-WSe2 artificial leaves. Our first-principles calculations demonstrate that reconstructed and imperfect edge configurations enable CO2 binding to form linear and bent molecules. Experimental results show that the solar-to-fuel quantum efficiency is a reciprocal function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…Since the edge contains zigzag (ZZ), antenna (An), and armchair (AC) configurations, the actual perimeter of a flake is inherently larger than that measured based on optical microscopy images. 160 The photo-induced carriers arriving at the surface of the photocatalysts play a crucial role in the catalytic reaction. The surface photovoltage spectroscopy (SPV) measurement is employed to investigate the separation and transport behavior of photoinduced charge carriers based on Kelvin probe force microscopy.…”
Section: Advanced Microscopic Techniquesmentioning
confidence: 99%
“…Since the edge contains zigzag (ZZ), antenna (An), and armchair (AC) configurations, the actual perimeter of a flake is inherently larger than that measured based on optical microscopy images. 160 The photo-induced carriers arriving at the surface of the photocatalysts play a crucial role in the catalytic reaction. The surface photovoltage spectroscopy (SPV) measurement is employed to investigate the separation and transport behavior of photoinduced charge carriers based on Kelvin probe force microscopy.…”
Section: Advanced Microscopic Techniquesmentioning
confidence: 99%
“…S24 (ESI†), the overall absorption percentage ( β AM1.5G ) is estimated to be 21.1% by using the following equation,where λ [nm], A ( λ < λ g ), and ϕ AM1.5G ( λ ) [W cm −2 nm −1 ] are the wavelength, absorption, and incident photon flux, respectively. 50,57 The results show that the ABAPE reaches and 0.43% (or ABPE = 0.09%) at 1.11 V RHE , respectively, which is in the same order of the highest productivity plants that have a typical efficiency of ∼1% annually (inset of Fig. S25a, ESI†).…”
Section: Resultsmentioning
confidence: 78%
“…where A 0 , A, erf(t), t, t 0 , s, and s are the constant offset, normalized radiative recombination coefficient, error function, time, starting decay time, standard deviation accounting for the instrument response function (IRF), and recombination time scale. 49,50 P1 and P2 show higher recombination times of 0.38 and 0.36 ns than P3, which is 0.27 ns, respectively (Fig. 4d).…”
Section: Optical Propertiesmentioning
confidence: 93%
“…As speculated, the precursor TPA1, which mainly absorbed UV light, almost showed no photocatalytic reactivity (Table 2, entry 7). Moreover, control experiments revealed that in the absence of TPA-MPs, visible-light, air or citric acid, the reaction proceeded rather sluggishly and only a small amount of the product was obtained (Table 2, entries [8][9][10][11]. These control experiments demonstrated that the TPA-MP catalyst, visible-light, air and citric acid decisively contribute to the photocatalytic reaction.…”
Section: Synthesis and Characterization Of Tpa-mpsmentioning
confidence: 97%
“…4 Thus, it is still highly desirable to develop efficient heterogeneous photocatalysts that are free of precious metals, inexpensive, stable, and recyclable, to decrease the processing costs in large-scale synthesis. 5 To this end, nonprecious metal-based semiconductors (such as bismuth-based nanomaterials, 6 metal sulfides, 7 metal oxides, 8 transition metal dichalcogenides, 9 etc. ) have emerged as promising candidates for replacing expensive and toxic precious metal-based complexes and organic dyes, which, however, are facing problems such as limited visible-light absorption and photocorrosion.…”
Section: Introductionmentioning
confidence: 99%